2009
DOI: 10.1002/cbic.200800834
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bonds versus Trp⋅⋅⋅Trp Pairs in Irregular β‐Hairpins: NMR Structure of Vammin Loop 3‐Derived Peptides as a Case Study

Abstract: Structural studies on model peptides have led to a good understanding of the rules behind the formation and stability of regular beta-hairpins. To test their applicability to the successful design of irregular beta-hairpins with long loops and/or beta-bulges at the strands, we mimicked loop 3 of vammin, a 4:6 beta-hairpin with a non-Gly beta-bulge. The most stabilising cross-strand pairs, disulfide bonds or/and TrpTrp pairs, were incorporated at non-hydrogen-bonded sites in peptides spanning the 69-80 region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 74 publications
0
63
0
Order By: Relevance
“…The ␤5-␤6 hairpin region has already attracted the interest of other research groups who reported the design of receptor antagonist peptides based on the ␤-hairpin region of VEGF (36 -38) and vammin (39). The HPLW peptide differs from the previous peptides in the starting sequence, which is based on the PlGF sequence 87-101, and most notably in the biological activity: HPLW is a VEGF receptor agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ␤5-␤6 hairpin region has already attracted the interest of other research groups who reported the design of receptor antagonist peptides based on the ␤-hairpin region of VEGF (36 -38) and vammin (39). The HPLW peptide differs from the previous peptides in the starting sequence, which is based on the PlGF sequence 87-101, and most notably in the biological activity: HPLW is a VEGF receptor agonist.…”
Section: Discussionmentioning
confidence: 99%
“…To stabilize the ␤-hairpin by a hydrophobic cluster, we replaced the natural amino acids (Lys 90 , Ser 98 , and Val 100 ) with aromatic residues. Differently from Mirassou et al (39), in HPLW, the aromatic residues were introduced in hydrogen-bonded positions. We were forced to use this approach as the non-hydrogen-bonded positions were occupied by the interacting residues.…”
Section: Discussionmentioning
confidence: 99%
“…One-dimensional spectra were acquired using 32 K data points, which were zero-filled to 64 K data points before performing the Fourier transformation. Phase-sensitive two-dimensional correlated spectroscopy (COSY), total correlated spectroscopy (TOCSY), and nuclear Overhauser enhancement spectroscopy (NOESY) spectra were recorded by standard techniques using presaturation of the water signal and the time-proportional phase incrementation mode, as reported previously (39). NOESY mixing times were 150 ms, and TOCSY spectra were recorded using 60-ms DIPSI2 with z filter spin-lock sequence.…”
Section: Methodsmentioning
confidence: 99%
“…NOESY mixing times were 150 ms, and TOCSY spectra were recorded using 60-ms DIPSI2 with z filter spin-lock sequence. For the samples in 25% HFIP, 1 H- 13 C heteronuclear single quantum coherence (HSQC) spectra were acquired at 13 C natural abundance using standard pulse sequences (39). Acquisition data matrices were defined by 2048 ϫ 512 points in t 2 and t 1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One-dimensional spectra were acquired using 32 K data points, which were zero-filled to 64 K data points before performing the Fourier transformation. Phasesensitive two-dimensional correlated spectroscopy (COSY), total correlated spectroscopy (TOCSY), and nuclear Overhauser enhancement spectroscopy (NOESY) spectra were recorded by standard techniques using presaturation of the water signal and the time-proportional phase incrementation mode, as reported previously (42). NOESY mixing times were 100 or 150 ms, and TOCSY spectra were recorded using 60 ms DIPSI2 with z filter spin-lock sequence.…”
Section: Methodsmentioning
confidence: 99%